Rancang Bangun Aplikasi Penjualan Bahan Baku Pada PT. Indochito International Sidoarjo - Rachmawati, Indah Suryaning; Sunarto, M.J Dewiyani; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT. Indochito International Sidoarjo built in 1999, located in Jalan Raya Wed-Betro Gedangan, Sidoarjo. PT. Indochito International is a company that specializes in import-export and general trading business. The sales process is a process that always takes place within the company. Based on observations and interview, the company experienced problems in the sales process and perekapan report is still considered in general and not detailed, and the frequent occurrence of errors in recording and perekapan report because it is still done manually and the length of time required to run multiple processes in sales. To overcome the problem, it needs to be made Application Raw Material Sales at PT. Indochito International. Stages of making this application begins with orders, sales, payment and reporting. Once tested, the application of sales of raw materials, can produce accurate data, order data, sales data, payment data, and data report. Keywords: Application, Management letter, incoming letter, outgoing letter